2013
DOI: 10.1007/s00784-013-1084-2
|View full text |Cite
|
Sign up to set email alerts
|

Vomer flap for hard palate repair is related to favorable maxillary growth in unilateral cleft lip and palate

Abstract: These findings may improve treatment outcome by modifying the treatment protocol for patients with unilateral cleft lip and palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…One group, however, reported an increased incidence of fistula formation after vomeroplasty, and that this treatment modality was abandoned due to their findings. 20 We experienced a 9.1% complication rate after palatoplasty with previous vomer repairs. Both von Langenbeck repairs and the failure of previous vomer flaps were linked to the incidence of surgical complications in this study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…One group, however, reported an increased incidence of fistula formation after vomeroplasty, and that this treatment modality was abandoned due to their findings. 20 We experienced a 9.1% complication rate after palatoplasty with previous vomer repairs. Both von Langenbeck repairs and the failure of previous vomer flaps were linked to the incidence of surgical complications in this study.…”
Section: Discussionmentioning
confidence: 97%
“…19 There is exhaustive literature on the use of vomer flaps and the effect on growth. Some investigators have shown favourable growth, 10,20,21 while some have shown adverse or no significant difference when vomer flap was used for the early closure of the hard palate. 6,7,22 The rationale for using the vomer flap is to minimize scar formation by preventing extensive elevation of sub-periosteal flaps and the use of relaxing incisions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The use of a single layer VF, at the time of lip repair, has been considered to be particularly advantageous in terms of maxillary development and early separation of the nasal and oral cavities (Liao et al, 2014). The rationale for using a VF is to overcome the unfavorable results of scarring by minimizing the area of denuded palatal bone (Ganesh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Since Dr Samuel Noordhoof founded our Center more than 3 decades ago, we have evaluated cleft lip/palate patients’ outcomes based on clinical lip morphology, [12] nasal morphology, [1315] lip scar, [16] speech, [17] complication rates, [18] and facial growth. [19] All were clinical studies based on data from the perspective of clinicians. However, a patient's (and their parents’) own perception of their surgical or orthodontic treatment outcome(s) and impact on their quality of life is of great importance for research by a craniofacial team to be holistic and integrated.…”
Section: Discussionmentioning
confidence: 99%